2000
DOI: 10.1093/intimm/12.9.1337
|View full text |Cite
|
Sign up to set email alerts
|

Th1 versus Th2 cytokine profile determines the modulation of in vitro T cell-independent type 2 responses by IL-4

Abstract: We have previously demonstrated that stimulation of B cells by multivalent membrane Ig cross-linking, using dextran-conjugated anti-IgD mAb (alpha delta-dex), in the presence of cytokines, is an in vitro model for T cell-independent type 2 (TI-2) Ig secretory responses. Earlier studies have shown that IL-4 enhances IgM secretion upon stimulation with alpha delta-dex plus IL-5 and induces IgG1 isotype-switching, without altering the proliferative response to alpha delta-dex. Here we show that IL-4 can have both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 61 publications
0
8
0
1
Order By: Relevance
“…Vos et al reported early and brief exposure (4 hours) of B cells to IL-4 enhanced a subsequent immunoglobulin secretory response but the continued presence of IL-4 during B cell stimulation suppressed antibody responses in a mouse model. 38 Whether our study findings are related to the results reported by Vos et al needs to be studied in the future.…”
Section: Discussionmentioning
confidence: 50%
“…Vos et al reported early and brief exposure (4 hours) of B cells to IL-4 enhanced a subsequent immunoglobulin secretory response but the continued presence of IL-4 during B cell stimulation suppressed antibody responses in a mouse model. 38 Whether our study findings are related to the results reported by Vos et al needs to be studied in the future.…”
Section: Discussionmentioning
confidence: 50%
“…Representative results from testing of eight anti-IL-4-specific clones and ten anti-IL-13-specific clones are shown. in vitro, early and brief exposure of B cells to IL-4 enhances Ig secretory response to subsequent stimulation with dextranconjugated anti-IgD mAbs in the presence of Th1-dependent cytokines, while continuous exposure results in the inhibition of the response [16]. In accord with these data, the results here suggest a possibility for induction of high-zone T-B-cell tolerance that may explain the absence of increase in Ab response at total doses of immunizing cytokines beyond 100 g. In particular, blocking effect of high doses of cytokines on differentiation and Ag-presenting function of dendritic cells [30] may be responsible for induction of such T-B-cell tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…IL-4-and IL-13-deficient mice show impaired development of Th2 cells [7,8,15] that produce a panel of cytokines favoring humoral immune response, including IL-4 and IL-13 [16]. Because IL-4 and IL-13 use common ␣-receptor chain and share many biological activities, such as participation in B-cell development and switching of Ig synthesis [17][18][19][20], IL-4KO mice and IL-13KO mice demonstrate several common defects in Ig synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…108 Several mouse and human studies have showed that asthma status, house-dust mite sensitization, and Th2 cytokines impair humoral immune responses to S. pneumoniae, H. influenza , and B. pertussis. 109-112 …”
Section: The Potential Mechanismsmentioning
confidence: 99%